Accuracy of Pregnancy Diagnosis with Commercially Available Progesterone Kit in Dairy Cows - Sah, A.K.; Bastola, R.; Pandeya, Y.R.; Pathak, L.; Acharya, M.P.; Khanal, D.R. (Nepalese Veterinary Journal, 2017)
Present study was carried out for the accuracy of commercially available progesterone ELISA kit at NCRP farm in the fiscal year 2015/16. Twenty crossbred Jersey and Holstein dairy cows were selected at different time periods of post insemination. Blood serum was collected in those animals and progesterone was quantified with the commercially available progesterone ELISA kit. Pregnancy diagnosis was performed by rectal palpation and Ultrasonography (USG) as a Gold standard and compared for the accuracy to ELISA kit. Results of the ELISA kit revealed the accuracy of the kit to be only 80 % with high sensitivity 92 % and very low specificity 57 % at 95 % confidence interval. Out of twenty artificially inseminated cows, thirteen were pregnant and seven were non-pregnant by the Gold standard test with their significantly different mean progesterone (at P < 0.05) 8.93±1.10 ng/ml and 4.36±1.21 ng/ml respectively. Hence, it can be used in the early pregnancy diagnosis at only after 24 days of the insemination, however, progesterone quantification by ELISA is not the confirmatory tests for the pregnancy diagnosis as this results accuracy of only 80 %.